Pengaruh Budaya Sunda pada Karakter Siswa MTs Alhuda Cicurug Sukabumi - Sumarlin, Denden; Komara, Endang; Koswara, Nandang; Helmawati, Helmawati (An-Nuha, 2025)
This study aims to analyze the influence of Sundanese local culture implementation on the character development of students at MTs Alhuda Cicurug, Sukabumi. The research background is based on the importance of character education rooted in local wisdom as a response to globalization and the erosion of traditional values among the younger generation. A quantitative approach was employed using a survey method and an ex-post facto correlational design. The research instrument was a closed-ended questionnaire using a Likert scale distributed to 100 student respondents. Data were analyzed using descriptive and inferential statistics through Pearson correlation and simple linear regression tests. The results showed a significant and positive influence between Sundanese local culture and students’ character education. The coefficient of determination (R²) value of 0.7455 indicates that 74.55% of the variation in student character is influenced by the implementation of Sundanese local culture in the school. The regression coefficient value of 0.9307 further supports the finding that the more the local culture is applied, the stronger the students’ character development. These findings reinforce previous research and expand it to the context of Islamic junior high schools (madrasahs), which have rarely been studied quantitatively. This research contributes both theoretically and practically to the development of a local culture-based character education model within madrasahs. It is recommended that schools actively integrate local wisdom values into both learning and extracurricular activities. Furthermore, a data-driven quantitative approach strengthens the legitimacy of future policy-making in character education. Keywords: Sundanese local culture, character education, madrasah, students, quantitative approach